The complexes of antibiotics with trace metals = Kompleksy antybiotyków z metalami śladowymi - Piontek, Marlena; Fedyczak, Zuzanna; Łuszczyńska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article, basing on the available literature, summarizes the results of physiochemical research into the structure of complexes of trace metals with antibiotics. It presents the leading methods of instrumental analysis applied to determine the structure of complexes.
Keywords: antybiotyki; metale śladowe; kompleksy metali śladowych; analiza instrumentalna; antibiotics; trace metals; complexes of trace metals; instrumental analysis